Cost benefit analysis of lighting retrofit of led bulb at Bangunan Ilmuan UiTM Campus Bukit Besi / Muhammad Badrul Amin Amran - Amran, Muhammad Badrul Amin (2022)
This study presents potential energy savings, life cycle cost analysis and payback period for lighting systems in Bangunan Ilmuan UiTM Bukit Besi. According to the results of a questionnaire survey, almost 90% of the lighting systems on the Bangunan Ilmuan UiTM Bukit Besi are made up of fluorescent lights. From the perspective of potential energy savings, cost-benefit analysis, life cycle cost analysis and payback period were conducted to convert to a more efficient lighting system. Therefore, lighting systems must be designed to be suitable to achieve the desired level of lighting while using minimal power. Lighting accounts for up to a third of power consumption in office buildings. The rational use of electricity in buildings is a very important and relevant topic, especially if excessive use, where energy is increasingly expensive, can cause climate change through high emissions of greenhousegases.